A behavioral perspective on service center routing: The role of inertia. Issue 8 (8th August 2021) - Schecter, Aaron; Wowak, Kaitlin D.; Berente, Nicholas; Ye, Han; Mukherjee, Ujjal
Abstract: Research on service center routing has largely assumed either fully codified automated routing, rational routing agents who can optimally route calls, or both. In practice, however, many routing scenarios are not fully codifiable, and human routing agents will likely exhibit biases in their routing decisions. In this paper, we explore the presence of behavioral inertia in service center routing. Inertia in this context is the propensity for routing agents to route issues more frequently to other agents with whom they have experience, rather than optimally routing those issues. We leveraged a unique dataset of more than 70, 000 routing decisions in a complex service operations context to examine the presence of inertia and associated performance implications. We find that, overall, inertia hurts performance, but in certain situations can be beneficial. Inertia increases the probability of issue resolution when agents exhibit inertial behavior in routing to other agents with high expertise, and inertia positively impacts (decreases) service time for particularly difficult, complex customer issues. This study contributes to research in service center operations by studying a previously unexplored phenomenon of inertia in routing by human agents and provides valuable insights to practitioners who manage service centers.